The Terror-Famine Trauma Through the Narrative of Novella "Holodomor" by Yevhen Hutsalo - Natalia Maftyn (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
One of the tasks of modern humanities, in particular Ukrainian one, is textualization of trauma as a memory that comes to life in “narratives of national identity”, since all the traumatic experience of previous generations, reflected on the mental map of Ukrainians, still remains not fully textualized, the whole situation is exacerbated by a new genocide, unleashed by Muscovy (Russia) against Ukraine. This article is devoted to the analysis of the novella “Holodomor” by Yevhen Hutsalo as a narrative of the collective trauma of the Holodomor, a terrible crime of the Moscow-Bolshevik dictatorship. The "trauma studies" methodology helps to research the narrative strategy, temporal-spacial modeling, ideological and literary sense of macro- and micro-images.